An investigation of rare earth elements in sewage sludge generated in Poland - Kostrz-Sikora, Paulina (Geology, Geophysics and Environment, 2024)
According to Statistics Poland, an average of around 1 million tonnes DM of sewage sludge has been generated in Poland annually over the past several years, of which approximately 30% has been used in nature, e.g. in agriculture, to grow plants for compost production, or for land reclamation (Statistics Poland 2004–2022). Most research on sewage sludge has focused on investigating its fertilizing value (nitrogen, phosphorus), identifying the composition of organic matter and determining the total content of heavy metals (including primarily cadmium, copper, nickel, lead, zinc, mercury and chromium) and the forms of their occurrence that determine their mobility and bioavailability. The occurrence of rare earth elements (REEs) in sewage sludge has hardly been addressed in research, even though their presence in production processes and everyday objects is increasingly common. The results presented in this article of studies of the concentrations of individual REEs in sewage sludge from selected industrial and municipal wastewater treatment plants located in Poland indicate that they are significantly lower than the average lanthanide level in the Earth’s crust. This may suggest that anthropogenic sources of REEs do not affect the composition of the wastewater and sludge studied. The calculated median concentration of ΣREE in sludge from industrial wastewater treatment plants is 9.47 mg/kg, whereas in municipal sewage sludge, the midpoint value for REE concentration is 13.5 mg/kg. Normalization of the obtained results with respect to Post-Archean Australian Shale (PAAS) and to topsoil and subsoil from Poland shows that the sludge is generally depleted in REE relative to the standards used. An assessment of the contamination of sewage sludge with rare earth elements, based on the calculated values of the geoaccumulation index (Igeo) for these elements, also shows that the content of lanthanides in the studied sewage sludge is lower than in the soils of Poland.